2020
DOI: 10.1212/wnl.0000000000010648
|View full text |Cite
|
Sign up to set email alerts
|

Whole-brain multimodal MRI phenotyping of periventricular nodular heterotopia

Abstract: Objective.To test the hypothesis that in periventricular nodular heterotopia (PVNH) structure and function of cortical areas overlying the heterotopic grey matter are preferentially affected.Methods.We studied a group of 40 patients with PVNH and normal-appearing cortex and compared their quantitative MRI markers of brain development, structure and function to 43 age- and sex-matched healthy controls. Inspired by models of neocortical development suggesting that neuronal migration follows a curvilinear path to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
(66 reference statements)
0
17
0
Order By: Relevance
“…Inter-areal coupling at different frequency bands is a general characteristic of the cortical network and is suggested to be an underlying mechanism of neuronal communications in both healthy 18,23,24 and epileptic 25 brains. Although previous fMRI studies have revealed the functional connectivity between the PVNH tissue and surrounding 7,9,[13][14][15]26,27 or distant 9,13 cortical areas, the oscillatory features of this connectivity are largely unknown. Using whole-brain MEG with high resolution in spectral, temporal, and spatial domains, the current study has found two prominent characteristics of the PVNH-cortical coupling in the resting state, which indicate that the PVNH tissue is functionally integrated into neocortical circuits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-areal coupling at different frequency bands is a general characteristic of the cortical network and is suggested to be an underlying mechanism of neuronal communications in both healthy 18,23,24 and epileptic 25 brains. Although previous fMRI studies have revealed the functional connectivity between the PVNH tissue and surrounding 7,9,[13][14][15]26,27 or distant 9,13 cortical areas, the oscillatory features of this connectivity are largely unknown. Using whole-brain MEG with high resolution in spectral, temporal, and spatial domains, the current study has found two prominent characteristics of the PVNH-cortical coupling in the resting state, which indicate that the PVNH tissue is functionally integrated into neocortical circuits.…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6] Although the PVNH tissue may become involved in generating seizures, [7][8][9][10][11] recent functional magnetic resonance imaging (fMRI) studies suggested a functional role of the PVNH tissue by finding interactions between the PVNH tissue and the neocortex. 9,[12][13][14][15][16] However, electrophysiological evidence supporting the functional role of the PVNH tissue is rare. In a recent study, using stereo-electroencephalography (sEEG) recordings, it was shown that PVNH tissues not only exhibited spontaneous activities which were correlated to the neocortex, but also generated normal physiological responses during a cognitive task in three patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hippocampal abnormalities are frequently associated with cortical malformation, up to 70% of patients with NH in some studies, 18,39 which raises the question of a dual pathology. A quantitative and functional MRI study found an increased complexity of the parahippocampal cortex correlated with hippocampal malrotation indices while those regions did not overlap with the HN overlying cortex 18 . However, even when temporal lobe structures are involved in the seizures, temporal lobe resection is usually unsuccessful 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative MRI also showed cortical thickening preferentially in cortices overlying the HN, which co-localized with areas of abnormal function identified with restingstate fMRI. 18 A few case reports used cortico-cortical evoked potentials (CCEPs) to study NH functional connectivity 19,20 or to help localize small NH scattered in the white matter. 21 Some noninvasive reports, using fMRI and magnetic transcranial stimulation with simultaneous scalp EEG, suggested that the existence of functional connectivity between NH and normotopic structures could predict the epileptogenicity of the network, 17,22 but this hypothesis has not been formally evaluated using invasive EEG recordings.…”
Section: Introductionmentioning
confidence: 99%
“…MRI is a commonly used neuroimaging method in periventricular nodular heterotopia. On MRI scans, multilobar cortical thickening encompassing prefrontal, latero-basal temporal and temporoparietal cortices may be seen [ 40 ]. Resting-state fMRI enables the detection of areas of abnormal function.…”
Section: The Most Common Imaging Abnormalitiesmentioning
confidence: 99%